Experimental comparison of devices thermal cycling in direct matrix converters (DMC) and Indirect Matrix Converters (IMC) using SiC MOSFETs - Trentin, Andrew; Zanchetta, Pericle; Empringham, Lee; De Lillo, Liliana; Wheeler, Patrick; Clare, Jon C. (2016)
This paper presents an experimental comparison between a Direct Matrix Converter and an Indirect Matrix Converter in terms of semiconductor devices thermal cycling. Both converters have been designed and built using SiC MOSFETs; the Indirect Matrix Converter has also been tested using a hybrid solution with Silicon IGBT on the input stage and SiC MOSFETs on the output stage.